2021
DOI: 10.1007/s00296-021-04812-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes in patients with familial Mediterranean fever: a retrospective cohort study

Abstract: Aim of this study is to investigate the course of coronavirus disease 2019 (COVID-19), in our cohort of familial Mediterranean fever (FMF) patients in means of mortality, admission to hospital and/or intensive care unit and length of hospital stay.A retrospective cohort was formed from patients who have previously been followed with a diagnosis of FMF. Patients of this cohort were retrospectively evaluated for a positive severe acute respiratory syndrome-coronavirus 2 (SARS-CoV 2) polymerized chain reaction (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The small number of patients and the observational study design with no controls are the major limitations of this study. Similarly, Güven et al retrospectively examined data from 34 FMF patients diagnosed with SARS-COV-2 between March and December 2020 in Turkey and their findings were in accordance with the above-mentioned study [ 74 ]. In addition, Gendelman et al retrospectively investigated 14,520 subjects from the Maccabi Health Services database in Israel (from 23 February 2020 to 31 March 2020) and found no difference in the rate of COVID-19 infection between colchicine users and non-users [ 75 ].…”
Section: Colchicine and Covid-19 Infectionsupporting
confidence: 67%
“…The small number of patients and the observational study design with no controls are the major limitations of this study. Similarly, Güven et al retrospectively examined data from 34 FMF patients diagnosed with SARS-COV-2 between March and December 2020 in Turkey and their findings were in accordance with the above-mentioned study [ 74 ]. In addition, Gendelman et al retrospectively investigated 14,520 subjects from the Maccabi Health Services database in Israel (from 23 February 2020 to 31 March 2020) and found no difference in the rate of COVID-19 infection between colchicine users and non-users [ 75 ].…”
Section: Colchicine and Covid-19 Infectionsupporting
confidence: 67%
“…Autoinflammatory disorders were present in 54 patients infected with SARS-CoV-2 (8%), 39 with familial Mediterranean fever (FMF, 72%) [ 5 ▪ , 12 , 13 , 20 ]. The rate of ICU admission was 4% and CFR 6% ( n = 3) for the entire group, while both ICU admission rate and CFR were 3% ( n = 1) for FMF patients.…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
“…Despite this, CFR among APS-1 patients is like the whole group of immune dysregulation disorders, indicating that immune dysregulation diseases arising from distinct genetic causes can predispose to severe COVID-19. On the other hand, patients affected by autoinflammatory disorders do not seem to have a specifically higher risk of severe COVID-19 and have mostly a mild course [ 5 ▪ , 10 , 20 ]. One prediction would be that elevated production or action of type I interferon, as one of the inflammatory mechanisms, provides effective innate host defense against SARS-CoV-2 infection, thereby minimizing disease severity.…”
Section: Severity Of Coronavirus Disease 2019 In Patients With Different Types Of Inborn Errors Of Immunitymentioning
confidence: 99%
“…Two papers from Turkey were published recently [ 28 , 29 ]. First paper reported three FMF patients with mild COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Second paper is a retrospective cohort study from a single center. It was found that comorbidities and disease severity were numerically high in hospitalized COVID-19 patients with FMF [ 29 ]. However, without statistical analysis, no estimation could be made in terms of factors associated with poor COVID-19 outcomes in patients with FMF.…”
Section: Discussionmentioning
confidence: 99%